Caracterización fisiológica y bioquímica del fruto de guayaba durante la maduración - María Soledad Hernández; Melgarejo, Luz Marina; Morales, Alicia Lucía; Fernández Trujillo, Juan Pablo; Solarte, María Elena (Universidad Nacional de Colombia, 2018)
Guayaba-Psidium guajava